Accurate analysis of mood detection using eye-images rather than facial expression recognition (FER) - Hossain, Arafat; Chakraborty, Akash; Syara, Syeda Rifa; Rahman, Saadman; Tanmoy, Fahad Muntasir (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.